THE IDEA OF FEMALE CIVILIZING MISSION IN EARLY STAGE OF BRITISH IMPERIAL EMIGRATION (30-50-s OF THE XIX-th c.) - Natalia D. Kryuchkova (Вестник Северо-Кавказского федерального университета)
The article deals with the formation of the conception of women`s civilizing mission in the early-Victorian period. The idea of female moral influence, based on the doctrine of «separate spheres» and evolutionary beliefs of the epoch, opened the imperial space for women. The author focuses on the Victorian discourses on female emigration, that are analyzed in terms of the concept of «civilizing mission».